Dynamic Transcriptome Analysis Reveals Complex Regulatory Pathway Underlying Induction and Dose Effect by Different Exogenous Auxin IAA and 2,4-D During in vitro Embryogenic Redifferentiation in Cotton - Fan, Yupeng; Tang, Zhengmin; Wei, Junmei; Yu, Xiaoman; Guo, Huihui; Li, Tongtong; Guo, Haixia; Zhang, Li; Fan, Yijie; Zhang, Changyu; Zeng, Fanchang (Frontiers in Plant Science, 2022)
Plant somatic cells can reprogram into differentiated embryos through somatic embryogenesis (SE) on the condition of plant growth regulators (PGRs). RNA sequencing analysis was performed to investigate transcriptional profiling on cotton redifferentiated callus that was induced by different auxin types (IAA, 2,4-D), different concentrations (0 mg L-1, 0.025 mg L-1, 0.05 mg L-1) and different incubation times (0 days, 5 days, 20 days). Under the 2,4-D induction effect, signal transduction pathways of plant hormone were significantly enriched in the embryogenic response stage (5 days). These results indicated that auxin signal transduction genes were necessary for the initial response of embryogenic differentiation. In the pre-embryonic initial period (20 days), the photosynthetic pathway was significantly enriched. Most of differentially expressed genes (DEGs) were down-regulated under the induction of 2,4-D. Upon the dose effect of IAA and 2,4-D, respectively, pathways were significantly enriched in phenylpropanoid biosynthesis, fatty acids metabolic, and carbon metabolic pathways. Therefore, primary and secondary metabolism pathways were of critical in cotton SE. These results showed that complex synergistic mechanisms involving multiple cellular pathways were the cause of the induction and dose-effect of auxin-induced SE. This study reveals a systematic molecular response to auxin signals, and the molecular pathway that regulates embryogenic redifferentiation during cotton SE.